THE IMAGE OF BIRDS IN THE WORKS OF ABDULLA ORIPOV - Ravshonbekova Gulmira (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. This article analyzes the artistic and symbolic interpretation of bird imagery in the poetry of the People’s Poet of Uzbekistan, Abdulla Oripov. It examines the ideological-aesthetic meaning, human emotions, aspirations, and spiritual values expressed through various bird symbols found in the poet’s works. The harmony between the image of birds in his poetry and their place in folk oral creativity and national thinking is also explored.